Effect of exposure time to smartphone apps on passing decision-making in male soccer athletes - Fortes, L. S.; Lima-Junior, D.; Nascimento-Júnior, J. A.; Costa, E. C.; Matta, M. O.; Ferreira, M. E. C. (Psychology of Sport and Exercise, 2019)
Background: Soccer is a dynamic sport of high unpredictability that requires appropriate decision making for success, but intervening factors such as exposure time to smartphone applications can lead to a decline in cognitive performance and consequently in psychomotor tasks. Purpose: The objective of this study was to analyze the effect of exposure time to smartphone applications on the passing decision-making performance in professional soccer athletes. Method: The participants were 20 soccer athletes aged 18-35 years (M = 24.7 ± 3.6). This study was a controlled and randomized experimental within-subject investigation, consisting of four visits with a 1-week interval. Male soccer athletes participated in four randomized conditions throughout the four visits: control (CON), 15-min smartphone (15SMA), 30-min smartphone (30SMA), and 45-min smartphone (45SMA). The Stroop Task assessed the level of induced mental fatigue before and after each experimental condition. Then, the athletes played a simulated soccer game. The game was filmed for further analysis of passing decision-making performance. Results: A condition effect (p < .001) was identified for passing decision-making performance, with impairment in 30SMA (p = .01, h2 = 0.6) and 45SMA (p = .01, h2 = 0.6) conditions. Conclusion: We conclude that at least 30 min of smartphone application exposure caused mental fatigue, which impaired passing decision-making performance in male soccer athletes.